Meta-Analysis of the Effectiveness of Implementing Interactive Ethnomathematics-Based Learning Media - Dyah Arum Puspanaja; Bambang Sri Anggoro; Rosida Rakhmawati M (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study aims to analyze the effectiveness of ethnomathematics-based interactive learning media on students’ mathematical cognitive abilities using a meta-analysis approach. The data were obtained from 32 studies that met the inclusion criteria. Effect sizes were calculated using the standardized mean difference with a random-effects model to account for variability across studies. The results of the meta-analysis indicate that ethnomathematics-based interactive learning media have a strong positive effect on students’ mathematical cognitive abilities, with an overall effect size of g = 1,48, which is classified as large. These findings suggest that integrating cultural contexts into interactive learning media is effective in enhancing students’ understanding and cognitive performance in mathematics learning.